The Effects of Workload, Teacher Commitment, and Principal Leadership on Teacher Productivity at High Schools in Mandau Subdistrict, Bengkalis Regency - Rika Rahma Laila Syahri; Maya Novita Sari (Journal of Educational Sciences, 2026)
This study examined the effects of workload, teacher commitment, and principal leadership on teacher productivity in senior high schools across Mandau District, Bengkalis Regency. A quantitative survey approach was employed involving 175 teachers selected through proportional random sampling. Data were collected using a four-point Likert-scale questionnaire, with all items confirmed to be valid and reliable. The data were analyzed using descriptive statistics, assumption testing, simple linear regression, and multiple linear regression. The findings revealed that workload, teacher commitment, and principal leadership each had a significant positive effect on teacher productivity (p < 0.05). Simultaneously, the three variables also significantly predicted teacher productivity. The coefficient of determination showed an R² value of 0.830, indicating that 83.0% of the variance in teacher productivity was explained by workload, teacher commitment, and principal leadership, while the remaining 17.0% was influenced by other factors outside the research model. These findings suggest that balanced workload management, stronger teacher commitment, and effective principal leadership play essential roles in improving teacher productivity. Therefore, schools should prioritize these factors to enhance teachers’ performance and overall educational quality. Further studies are recommended to explore additional variables influencing teacher productivity and to strengthen the generalizability of the findings.